Пепельное небо: [роман] / Александр Конторович - Конторович Александр Сергеевич (Эпицентр, 2011)
Экземпляры: ф.6 (20200305) / Инвентарный номер: 3399 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445